HUBUNGAN IKLAN OBAT DEMAM DI TELEVISI DENGAN KEPUTUSAN SWAMEDIKASI DI ERA PANDEMI COVID-19 PADA MASYARAKAT DI DUSUN SIDOROGO RT 03 RW 06 - Fahmi Ardianti Purnawiranita (AFAMEDIS, 2021)
The COVID-19 pandemic is an outbreak condition caused by the COVID-19 virus that spreads in various regions throughout the world. As a result of this pandemic, the government issued a new policy, namely PSBB (Large-scale Social Restrictions). Self-medication is generally done to treat mild symptoms. One of the symptoms that appear during this pandemic is fever. Fever is not a disease but a symptom of various diseases. To carry out self-medication, correct and safe information is needed. Information can be obtained from various sources, one of which is television.Television advertising is the main source of information about drugs. The purpose of this study was to determine whether there was a relationship between advertisements for fever medicine on television and the decision to self- medication in the era of the covid-19 pandemic in the community in Sidorogo village RT 03 RW 06. This research method is a type of analytical research with a cross-sectional research design. This research was conducted in Sidorogo village RT 03 RW 06. The sampling technique was carried out using non-propability sampling, namely purposive sampling by considering inclusion and exclusion criteria and the number of respondents was 100 people. The instrument used comes from questionnaire data, which is filled out by respondents. Data analysis using Chi-square test. The results showed that the relationship between television advertisements for fever medicine and self-medication decisions had a significant p value of 0.000. The conclusion obtained is that there is a relationship between advertisements for fever medicine on television and the decision to self-medication in the era of the covid-19 pandemic in the community in Sidorogo village RT 03 RW 06. Keywords : Drugs advertisement, Fever, Self-medication, covid-19 pandemic